Characteristics of developmental activities among Chinese female football players: a comparative analysis between national and professional level - Wang, S.; Chen, Q.; Cai, H.; Li, P.; Liu, H. (Psychology of Sport and Exercise, 2026)
Objectives The purpose of this study was to investigate the developmental activities of Chinese female national and professional football players.